A campo cerrado: Bultos y canastillas (2023)
This project brings together each of the stages, including research and a portion of the files related to artistic exploration and conceptual reflections. Titled 'In Closed Field: Bundles and Baskets,' it consists of an illustrated album, an artist's book, three installations, and an academic paper. This work addresses the notion of inhabiting through a process of research-creation in the Ubaté market square. Spaces of memory, daily life, and the knowledge inherent to the activities of the place are explored through various artistic languages, such as illustration and installation, thereby connecting the possibilities of contemporary artistic practices. The approach was carried out through three drifts, during which material was collected for the project's development through photographs, conversations, and surveys.